2021
DOI: 10.1002/casp.2533
|View full text |Cite
|
Sign up to set email alerts
|

Emplacing linked lives: A qualitative approach to understanding the co‐evolution of residential mobility and place attachment formation over time

Abstract: Despite growing interest in issues of residential mobility and place attachment in a globalised world, research within Environmental and Community psychology has tended to overlook the ways that interpersonal relations, and wider socio‐political and economic structural factors inform place attachment formation amongst residentially mobile individuals. We address this gap drawing on the Human Geography concept of ‘Linked Lives’ (Coulter et al., Progress in Human Geography, 2016, 40(3), 352–374), to conceive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The three sections of attributes were treated as dependent variables, key explanatory variables and control variables. Second, key explanatory variables reflecting one's processual residential mobility in Shanghai were surveyed via questions regarding a series of local housing experiences in the past and present (Bailey et al, 2021). As per the literature, housing move, housing tenure type and housing access were considered as the main facts of residential mobility (Clark et al, 1984;Li, Mao, et al, 2019).…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The three sections of attributes were treated as dependent variables, key explanatory variables and control variables. Second, key explanatory variables reflecting one's processual residential mobility in Shanghai were surveyed via questions regarding a series of local housing experiences in the past and present (Bailey et al, 2021). As per the literature, housing move, housing tenure type and housing access were considered as the main facts of residential mobility (Clark et al, 1984;Li, Mao, et al, 2019).…”
Section: Measurementmentioning
confidence: 99%
“…A few studies have examined how residential stability increases neighbourhood attachment, and such studies warned that heightened mobility may diminish a fixed place attachment (Clark et al, 2017; Devine‐Wright, 2014). While previous studies have considered personal/residential mobility and subsequent changes in the living environment as threats or challenges to place attachment (Brown & Perkins, 1992; Manzo et al, 2008), recently, scholars have argued that the relationship between mobility and attachment is nonlinear and context‐dependent; thus, future studies need ‘a more processual and temporally dynamic conception of place attachment’ (Bailey et al, 2021, p. 516). This processual perspective highlights that formative place experiences in the past, such as significant events in residential mobility, can inform future place attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarship has described and provided empirical evidence of intensity and varieties of place attachment [12,[39][40][41]. Five ways in which people may relate to their places of residence have been identified.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There is ample evidence from different field studies that place attachment relates to a variety of different behaviors such as residential mobility [41], civic activism [12], social well-being [42], and pro-environmental behaviors and attitudes such as "environmental sentiment" [43] or a "care for the wilderness" [44] and park visitors' citizenship behavior [45].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, Walker and Chapman [42] and Williams and Vaske [43] treated place attachment as a two-dimensional concept that involved only place identity and place dependence. Bailey et al [44] investigated five types of relationship of a resident to place, which were traditional attachment, active attachment, place alienation, place relativity, and placelessness. Halpenny [45] and Stedman [46] argued that the conceptualization of place attachment reflects place dependence, place identity, and affective components, while Kyle et al [47] suggested that place attachment includes place identity, place dependence, and place social bonding.…”
Section: Literature Review 21 Place Attachmentmentioning
confidence: 99%